Laparoscopic Approach to Late-Presenting Traumatic Diaphragmatic Hernia: Case Report - Majo Meza, Jaime Oswaldo (2025)
Late-presenting traumatic diaphragmatic hernia is rare and most often caused by blunt trauma. It presents diagnostic challenges and controversial surgical management, which may involve thoracoscopic or laparoscopic approaches to close the defect and minimize the impact on the involved structures. This case reports a man diagnosed 15 years after an open trauma, successfully treated laparoscopically without complications, leading to early discharge and favorable recovery. The case supports the laparoscopic approach as an effective alternative for achieving adequate reduction of herniated abdominal contents and hemostatic control, followed by primary closure, depending on the defect size.